Clinical utility of 18F-FDG PET/CT in low 18F-FDG-avidity breast cancer subtypes: comparison with breast US and MRI. Issue 1 (January 2018) - Park, Hye Lim; Yoo, Ie Ryung; O, Joo Hyun; Kim, Hyoungwoo; Kim, Sung Hun; Kang, Bong Joo
Abstract : Objective: The aim of this study was to evaluate the diagnostic performance of fluorine-18-fluorodeoxyglucose ( 18 F-FDG) PET/CT in initial axillary lymph node (ALN) staging and tumor recurrence in breast cancer subtypes with low 18 F-FDG avidity in comparison with breast ultrasonography (US) and/or MRI. Patients and methods: A total of 491 PET/CT exams from 192 patients with biopsy-proven breast cancer subtypes with low 18 F-FDG avidity were enrolled retrospectively. Nodal status on staging and locoregional recurrence or metastasis on surveillance was confirmed either by pathology or by further clinical follow-up. Comparison was made with recent US and/or MRI. Results: A total of 142 scans were for staging and 349 scans were for surveillance. For the staging, 127 tumors had perceptible 18 F-FDG uptake. For the detection of ALN metastasis, the sensitivity, specificity, and accuracy were calculated to be 51.5, 94.6, and 84.7% for 18 F-FDG PET/CT, 42.4, 90.1, and 79.2% for US, and 51.5, 88.3, and 79.9% for MRI, respectively. PET/CT showed significantly higher specificity than MRI. In the surveillance, the total recurrence rate was 4.3%. There were no cases of recurrence of mucinous or tubular carcinoma. PET/CT showed comparable diagnostic performance for locoregional recurrence compared with US in invasive lobular carcinoma. Distant metastasis developed in five patients (one stage II, four stage III), and all of these were identified by PET/CT alone. Conclusion: PET/CT showed comparable diagnostic performance with US and/or MRI for ALN staging and detecting tumor recurrence even when the primary breast cancer has low 18 F-FDG avidity. 18 F-FDG PET/CT also detected unsuspected distant metastasis in 36.4% of stage III patients. Surveillance PET/CT should be considered in advanced-stage invasive lobular carcinoma for early detection of recurrence.